Exploring Nanomaterials: Synthesis, Characterization, and Applications in Solar Cells and Immunosensing - Jitendra Malviya; Anita Tilwari (Archives of Case Reports, 2025)
Nanomaterials have garnered immense interest due to their distinctive physical, chemical, and electronic properties, making them suitable for various innovative uses. This study focuses on synthesizing and characterizing these materials, highlighting their potential applications in immunosensors and dye-sensitized solar cells (DSSCs). Several techniques, like chemical vapor deposition and sol-gel methods, are employed to produce nanomaterials with the desired shape, size, and surface characteristics. To better understand their structure, chemistry, and optical behavior, advanced tools like X-ray diffraction and scanning electron microscopy are used. In solar cell applications, especially DSSCs, nanomaterials like titanium dioxide (TiO₂) significantly improve electron transfer and light absorption, enhancing energy conversion efficiency. In medical diagnostics, nanomaterials such as gold nanoparticles and graphene-based systems enhance the sensitivity and precision of immunosensors. This research underlines the broad applicability of nanomaterials in both biosensing and renewable energy. Future studies aim to develop multifunctional nanomaterials with integrated properties, offering pathways toward scalable and efficient technological solutions in renewable energy and biomedicine.